URGENCY OF THE PERSONAL DATA PROTECTION BILL ON PRIVACY RIGHTS IN INDONESIA - Giosita Kumalaratri; Yunanto yunanto (Jurnal Hukum, 2021)
The development of information technology in the era of globalization makes it easier for people to carry out their daily activities, apart from socializing, it can also be a channel for work. Behind the simplicity coveted by technological developments opens up loopholes related to personal data that is easily misused. Indonesia does not yet have specific laws governing the protection of personal data as a whole. So that the author will examine the urgency of the draft personal data law in Indonesia, personal data protection schemes, to the impact of the implementation of the personal data protection bill. This study uses a normative juridical research method. The results of the study point to a privacy rights protection scheme in which everyone has the right to publish personal data or the right not to publish personal data to the public. The weakness of personal data protection regulations in Indonesia that have not been specifically regulated increases the potential for crimes against the right to privacy, but the drafting of the Personal Data Protection Bill brings fresh air not only to the public but to the government sector to the international business environment.